2016
DOI: 10.17712/nsj.2016.2.20150472
|View full text |Cite
|
Sign up to set email alerts
|

Walk like me, talk like me

Abstract: Understanding social cognition has become a hallmark in deciphering autism spectrum disorder. Neurobiological theories are taking precedence in causation studies as researchers look to abnormalities in brain development as the cause of deficits in social behavior, cognitive processes, and language. Following their discovery in the 1990s, mirror neurons have become a dominant theory for that the mirror neuron system may play a critical role in the pathophysiology of various symptoms of autism. Over the decades,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 124 publications
(154 reference statements)
0
10
0
1
Order By: Relevance
“…However, future investigations must be done to look for the possibility of the existence of mirror neurons in cerebellum. If consistent research studies found the same findings as above then we would be able to claim with confidence that mirror neurons are damaged in autism because cerebellum contains MNS [Saffin & Tohid, ]. In addition, Fuentes and Bastian emphasize the role of the cerebellum in two processes that could be considered aspects of motor cognition [Fuentes & Bastian, ].…”
Section: Discussionmentioning
confidence: 52%
“…However, future investigations must be done to look for the possibility of the existence of mirror neurons in cerebellum. If consistent research studies found the same findings as above then we would be able to claim with confidence that mirror neurons are damaged in autism because cerebellum contains MNS [Saffin & Tohid, ]. In addition, Fuentes and Bastian emphasize the role of the cerebellum in two processes that could be considered aspects of motor cognition [Fuentes & Bastian, ].…”
Section: Discussionmentioning
confidence: 52%
“…It is tempting to speculate that astrocyte function may be the bottleneck of a possible suggestive answer to this question (Bianco-Suarez et al 2016). The neurobiological pattern of ASD has recently introduced the role of mirror neurons (Schulte-Rüther et al 2016, Linkovski et al 2016, Saffin and Tohid 2016. Mirror neurons exert direct action that impact the occipital cortex, cingulate cortex, insula and dorsal prefrontal cortex in ASD (Yang and Hoffmann 2015).…”
Section: Neuroinflammation and Neurobiology In Asdmentioning
confidence: 99%
“…However, the emergence of functional MRI (fMRI) has revolutionized the field of neuroscience, 11 enabling us to understand brain function with far greater precision, improving understanding of concepts involved in complicated topics such as the mirror neuron system. 12 Some of the most interesting findings of structural MRI and fMRI studies with schizophrenic patients include decreased gray matter (frontal lobe) volume, and reduced brain activity and volume. 13 The ventricles and the basal nuclei in the brains of schizophrenic patients are often found to be larger than normal, whereas the hippocampus and amygdala are found to be smaller.…”
Section: Disturbances In Cognitive Control Related To Prefrontalmentioning
confidence: 99%